The Influence of Disease Cues on Preference for Typical versus Atypical Products - Huang, Yunhui; Sengupta, Jaideep (Journal of Consumer Research, 2020)
Abstract This article examines how exposure to disease-related cues influences consumers’ preference for typical (vs. atypical) product options. Merging insights from evolutionary psychology with research on preference for typicality in consumer products, we predict that disease salience decreases relative preference for typical versus atypical options, because typical products are implicitly associated with many people, misaligning them with the people-avoidance motive triggered by disease cues. We further build on this conceptualization to identify situations in which this preference shift might be eliminated. Specifically, we argue that the focal effect will not manifest when the disease in question is explicitly described to be noncontagious, or when an anti-infection intervention is introduced, or when the decision context involves minimum infection. Results from six studies provide support for our predictions, advancing basic knowledge on the evolutionary strategies guiding disease avoidance, while also documenting how such strategies can affect consumer preferences.